Rearing techniques for calanoid copepod acartia spp. under laboratory condition - Jocson, Teresita Cayetano (College of Fisheries, University of the Philippines in the Visayas, 1992)
This study evaluated the abundance and developmental stage frequency distribution of Acartia spp. grown under three treatments ; pond water fertilized with chicken manure (basal application) and 16-20-0, Chlorella-fed and pond water fertilized with chicken manure (applied daily) only. Acartia spp. collected from brackishwater ponds were reared under laboratory condition, using either twelve white plastic basins or ice creamgallon containers with 5-3 liters of brackishwater or pond water. Four experiments were conducted and took about forty (40) culture days. The number of any developmental stage of Acartia spp. did not vary according to treatment (P>0.05) indicating that this copepod is not selective on the quality of food, it can subsist on any microscopic food within its digestive capacity. However at 2.0 cm deep of water Acartia spp. was most abundant in the chicken manure treatment while in the 8.5 cm depth of water the density of Acartia spp. was highest in that fed with Chlorella but comparing both densities, chicken manure-fed copepods was denser. Population densities were related to food abundance, Naupli, copepodite and adult male reached highest densities in the chicken manure treatment of 23, 10, and 17 ind/1 respectively. Egg-bearing and non-egg bearing adult females were most abundant in the chicken manure + 16-20-0 treatment of 5, and 18 ind/1 respectively. Temperature and food abundance played a critical role (P<0.01) on the growth and development of Acartia spp Salinity and water pH had significant effects (P<0.05) also. Dissolved oxygen was not significantly correlated (P>0.05) to the density of Acartia spp. This indicated that dissolved oxygen which ranged from 3.58 - 8.52 mg/1 was within favorable limits and that fluctuation of dissolved oxygen did not necessarily influence survival of growth of the population of this copepod.